Development of a MATLAB GUI Application for Computing Reliability Indices at an Electrical Substation - Fajri, Amrisal Kamal; Efendi, Erwan Tri; Evan, Bah; Prihatmini, Eri (Politeknik Negeri Semarang, 2025)
The reliability of power distribution systems plays a crucial role in ensuring the continuous and efficient supply of electricity to consumers. This study presents the development of a MATLAB-based Graphical User Interface (GUI) application designed to compute key reliability indices, including SAIFI (System Average Interruption Frequency Index), SAIDI (System Average Interruption Duration Index), and CAIDI (Customer Average Interruption Duration Index), specifically for electrical substations. The application was developed using MATLAB's App Designer and structured to provide an intuitive and interactive user experience. Real operational data from a 150 kV substation were utilized to test and validate the application’s functionality. The results demonstrate that the tool effectively simplifies the reliability analysis process, reduces calculation time, and minimizes the potential for manual errors. This application can serve as a practical support system for engineers and researchers in evaluating and improving the performance of electrical distribution systems.